Realization of GaN-based gain-guided blue laser diodes by helium ion implantation. (1st October 2019) - Zhang, Qi; Zhang, Shuming; Zhang, Feng; Hu, Junjie; Feng, Meixin; Ikeda, Masao; Li, Deyao; Liu, Jianping; Yang, Weiguang; Zhang, Liqun; Yang, Hui
Abstract: The fabrication process and characteristics of gallium nitride (GaN) based gain-guided blue laser diodes (LDs) are studied, in which an ion implantation process is adopted to confine carrier injection into the active region. The implantation of helium ions with an energy of 85 keV, an angle of 0°, and a dosage of 4.7 × 10 14 cm −2 is conducted in the experiment. The specific contact resistivity of p-type ohmic contact of implanted sample is determined to be 2.2 × 10 –4 Ω cm 2, which is comparable with the un-implanted sample. Then, both ion-implanted gain-guided and ridge waveguide LDs are fabricated at the same time. Similar threshold current density and slope efficiency are obtained, while the operation voltage of ion-implanted gain-guided LDs is 0.2 V lower than the ridge waveguide LDs at 0.56 kA cm −2 . The ridge waveguide LDs show multi-mode operation after lasing. However, for ion-implanted gain-guided LDs, the far-field pattern indicates a single lateral mode operation up to twice of the threshold current, and the peak optical output power of blue single mode LDs at 450 nm exceeds 200 mW under pulsed condition.